![Роман](https://sproshu.net/uploads/ava/1/ava6266.jpg)
Роман
6 год назад
Производные функции
g(x) = x^3+√2
y = 3x * tgx
ОТВЕТЫ
![Мирон](https://sproshu.net/uploads/ava/4/ava9873.jpg)
Мирон
Jul 1, 2019
G (x) = (x^3 + √2) = 3x^2
y = (3x*tgx) = (3x)tgx + (tgx)3x = 3tgx + 3x/cos^2x =
= 3(tgx + x/cos^2x).
y = (3x*tgx) = (3x)tgx + (tgx)3x = 3tgx + 3x/cos^2x =
= 3(tgx + x/cos^2x).
Я думаю, что так....
g(x) = (x^3+√2)= 3x^2
y= (3x*tgx)= (3x)tgx + (tgx)3x = 3tgx + 3x/cos^2x = 3(tgx + x/cos^2x)........))))
g(x) = (x^3+√2)= 3x^2
y= (3x*tgx)= (3x)tgx + (tgx)3x = 3tgx + 3x/cos^2x = 3(tgx + x/cos^2x)........))))
149